(untitled) (ҚазҰУ Хабаршысы. География сериясы, 2024)
The aim of our research is to show how Székesfehérvár, an industrial city in Hungary, can adapt to the challenges of the 21st century in the field of sustainability from the perspective of tourism. The city has launched a number of initiatives that directly address the sustainability of tourism. These projects include the expansion of green spaces, the promotion of environmentally friendly transport solutions and the protection of the local economy and heritage. A key element in the development of sustainable tourism is raising environmental awareness, which includes the organisation of educational programmes and community events to promote sustainable lifestyles among residents and visitors. Our research looked at how sustainability is integrated into the city’s tourism-related developments and how this approach is becoming a key element of urban development. In our analysis, we look in detail at specific projects and programmes that have been implemented in Székesfehérvár in the context of sustainability, and assess their effectiveness, challenges and reception by residents and tourists.